Revealed Preference, Rational Inattention, and Costly Information Acquisition - Caplin, Andrew; Dean, Mark (American Economic Review, 2015)
Apparently mistaken decisions are ubiquitous. To what extent does this reflect irrationality, as opposed to a rational trade-off between the costs of information acquisition and the expected benefits of learning? We develop a revealed preference test that characterizes all patterns of choice “mistakes” consistent with a general model of optimal costly information acquisition and identify the extent to which information costs can be recovered from choice data. (JEL D11, D81, D83)